(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article provides information about the Sijo genre, which appeared in Korea during the Joseon (Li) period of literature (1392-1910). This genre is considered to be a lyrical genre with a certain excitement and experience image, and it incorporates Korean folklore traditions and three religious-philosophical teachings of the people of the Far East (Confucianism, Buddhism and Taoism).